PERAN PONDOK PESANTREN DALAM MEMBANGUN KEMANDIRIAN EKONOMI BERBASIS PEMBERDAYAAN MASYARAKAT - Fathurrahman Al-Ghifari; Siti Humaira Nasution (Mukhtasab: Journal of Economics and Islamic Business, 2026)
The dependence of Islamic boarding schools (pesantren) on external assistance often hampers institutional development and missionary autonomy. This study aims to analyze the economic empowerment mechanism at Pondok Pesantren Modern "Nurul Ikhlas" and its impact on institutional independence and the community in Nagari Panyalaian. This research uses a qualitative field research approach with a case study method. Data were collected through in-depth interviews, observation of business units, and analysis of local economic documents. The study found that the pesantren successfully built independence through diversification of business units (agrotourism, retail, and services) managed professionally with Amanah values. The pesantren also acts as a business incubator for students and an off-taker for local products, supported by the optimization of productive Ziswaf funds. Pesantren functions as an effective Social Enterprise model in driving the community economy. This strategy recommends the need for management digitalization and halal certification support to strengthen the competitiveness of the pesantren economy in the digital era.